2007
DOI: 10.1105/tpc.107.051524
|View full text |Cite
|
Sign up to set email alerts
|

The GID1-Mediated Gibberellin Perception Mechanism Is Conserved in the Lycophyte Selaginella moellendorffii but Not in the Bryophyte Physcomitrella patens

Abstract: In rice (Oryza sativa) and Arabidopsis thaliana, gibberellin (GA) signaling is mediated by GIBBERELLIN-INSENSITIVE DWARF1 (GID1) and DELLA proteins in collaboration with a GA-specific F-box protein. To explore when plants evolved the ability to perceive GA by the GID1/DELLA pathway, we examined these GA signaling components in the lycophyte Selaginella moellendorffii and the bryophyte Physcomitrella patens. An in silico search identified several homologs of GID1, DELLA, and GID2, a GA-specific F-box protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
208
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 193 publications
(228 citation statements)
references
References 58 publications
14
208
2
4
Order By: Relevance
“…7): The common ancestor of basal land plants before the separation of the mosses had GAMYB-mediated regulation in the proto-tapetal cells (spore sac cells) and spores for spore outer wall formation. At this stage, the GAMYB-mediated regulation of spore outer wall formation was independent of the GA signalling pathway, as the GA signalling pathway had not yet been established 13,14 . Consistent with this hypothesis, it is reported that the disruption of multiple DELLA-like genes in P. patens did not affect the plant's life cycle 14 , and that the disruption of PpCPS/KS, which encodes ent-kaurene synthase, an enzyme essential for GA synthesis in flowering plants, did not result in abnormal spore development 36 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…7): The common ancestor of basal land plants before the separation of the mosses had GAMYB-mediated regulation in the proto-tapetal cells (spore sac cells) and spores for spore outer wall formation. At this stage, the GAMYB-mediated regulation of spore outer wall formation was independent of the GA signalling pathway, as the GA signalling pathway had not yet been established 13,14 . Consistent with this hypothesis, it is reported that the disruption of multiple DELLA-like genes in P. patens did not affect the plant's life cycle 14 , and that the disruption of PpCPS/KS, which encodes ent-kaurene synthase, an enzyme essential for GA synthesis in flowering plants, did not result in abnormal spore development 36 .…”
Section: Discussionmentioning
confidence: 98%
“…During the divergence of basal vascular plants including lycopods from the moss lineage, a GA receptor, GID1 and DELLA repressors were established as key components for GA perception system in association with a functional GA biosynthetic pathway, indicating the occurrence of the entire GA signalling pathway 13,14 . However, the biological function of GA in basal vascular plants has been unclear, as GA treatment does not cause any developmental defects at the vegetative stage, such as increased stem or leaf elongation, in Selaginella 13 . Therefore, we hypothesized that, in such basal vascular plants, GA may be exclusively involved in the outer wall development of microspores via GAMYB.…”
Section: Molecular Characterization Of Smgamyb and Ppgamybsmentioning
confidence: 99%
See 3 more Smart Citations